La economía tardorromana del Sureste peninsular: el ejemplo del Puerto de Mazarrón (Murcia) - Pérez Bonet, Mª Ángeles (Antigüedad y Cristianismo, 1998)
The Puerto de Mazarrón, about 30 kilometres from both Carthago Nova, to the east, and Aguilas, to the west, experienced from the fourth to sixth century AD, a spectacular economic development, principally by producing and selling fish sauces. This paper also documents the flowering of commercial relations with north Africa, in a similar way that Tarraconense did during the same period. A study of the types of North African Amphoras used shows clearly that olive oil was the main imported product. Because of the size and characteristics of the population this oil must have been re-exported.